Barriers to Clinical Research in Latin America - Chomsky-Higgins, Kathryn; Miclau, Theodore A.; Mackechnie, Madeline C.; Aguilar, Dino; Avila, Jorge Rubio; dos Reis, Fernando Baldy; Balmaseda, Roberto; Barquet, Antonio; Ceballos, Alfredo; Contreras, Fernando; Escalante, Igor; Elias, Nelson; et al. (Frontiers in Public Health, 2017)
Enhancing health research capacity in developing countries is a global health priority. Understanding the orthopedic burden of disease in Latin America will require close partnership between more-developed and less-developed countries. To this end, the Osteosynthesis and Trauma Care Foundation assembled a research consortium of Latin-American orthopedic leaders. Prior to the meeting, we surveyed attendees on perceived barriers to conducting research at their institutions. During the event, working groups discussed these barriers, developed strategies for addressing them, and planned future steps for collaboration. The participants established the need for global relationships that allow colleagues from Latin America to access to training and established investigational infrastructure of North American centers to address research questions relevant to their communities. As a result of the discussion, the International Orthopaedic Multicenter Study (INORMUS) in Fracture Care was initiated. Since then, an expanded international working group, Associación de Cirujanos Traumatológicos en las Americas (ACTUAR), has been created with the purpose of promoting increased global partnership for research capacity development.